2020
DOI: 10.1097/rhu.0000000000001553
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Cellular Profile as a Biomarker for Lupus Nephritis

Abstract: Background/ObjectiveA search for the ideal biomarker for lupus nephritis (LN) is still underway, one that can be used for early detection and correlate with the class and activity of LN. Urine is normally devoid of leukocytes; however, it has been observed that macrophages and T lymphocytes are routinely present in the urine of LN patients and those with other proliferative renal diseases. This provides the idea for their potential use as biomarkers for proliferative LN. Here, we measured the urinary CD4+, CD8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…In the current study, CD4/CD8 ratio showed significant decrease between patients and controls with inversed signeficant correlation to disease activity. Agreed with our results Robinson et al [27], Sonawale et al study [11], Shah et al study [30] and Jiang et al study [31] In the present study we found low CD4/CD8 ratio was not correlated with LN and against our results El-Girby et al [32] and Kopetschke et al study [33].…”
Section: Discussionsupporting
confidence: 83%
“…In the current study, CD4/CD8 ratio showed significant decrease between patients and controls with inversed signeficant correlation to disease activity. Agreed with our results Robinson et al [27], Sonawale et al study [11], Shah et al study [30] and Jiang et al study [31] In the present study we found low CD4/CD8 ratio was not correlated with LN and against our results El-Girby et al [32] and Kopetschke et al study [33].…”
Section: Discussionsupporting
confidence: 83%
“…The CD14 (C-159T) polymorphism was related to increased susceptibility to SLE and could be a promising biomarker for the diagnosis of lupus nephritis (40). Moreover, a study demonstrated that urinary CD14 mononuclear cells could serve as a biomarker for lupus nephritis (LN) (41). The enzyme indoleamine 2,3-dioxygenase 1 (IDO1) is a heme enzyme that regulates immune responses to arrest inflammation (42).…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have also described CD14 + cells as a major population in the urine of LN. CD14 + cells were more abundant in LN compared to non-renal SLE and healthy controls, and associated with class IV but not in class III nephritis [62]. More precisely, Kim et al [63], found higher numbers of CD11c + macrophages in the urine of patients with proliferative LN, with a strong association with the serum anti-dsDNA titers and chronicity indexes.…”
Section: Cell-associated Biomarkersmentioning
confidence: 95%
“…It may indicate patients at increased risk for long-term renal function loss [57]. ALCAM levels correlated positively with activity index [58] Effective LN therapy reduced uVCAM-1 levels over the time [56] Leukocytes Monocytes/macrophages in proliferative LN [62][63][64] Higher eosinophils numbers in LN [65] CD4+CD25-Foxp3+ T cells in active LN [66] CD4+ and CD8+ T cells in active LN [67,68] Th17 associated with less severe disease [69] pDC and PB/PC in severe LN [70,71] Lower numbers of CD8+ T cells in remission [67,68] Soluble leukocyte marker sCD163 in active LN [72,73], mostly in proliferative classes [74] sCD11b correlates with histological activity [75] T-bet mRNA in higher in active LN [76,77] sCD163 increases from 6 months before flare [78] Higher T-bet mRNA gives higher risk of severe flare [77] sCD163 decreases after treatment in drug responders [73,78] sCD11b decreases with clinical remission [75] However, other studies failed to detect anti-dsDNA antibodies. Yamada et al [79], studied the presence of anti-dsDNA in serum and urine of nine SLE patients presenting heavy proteinuria.…”
Section: Autoantibodiesmentioning
confidence: 99%